XML Demystified : - Keogh, Jim (McGraw-Hill, 2005)
The book begins by introducing you to the building blocks of XML. Then, you'll learn about XML documents, document type definitions (DTDs), XML schema, XLink, XPath, XPointer, XSLT, XML parsers, RSS, XQuery, and MSXML. Featuring end-of-chapter quizzes and a final exam, this book will have you creating XML applications in no time.